Religious community architecture a descriptive study on the episcopal polity of Roman Catholic church complexes in diocese of Tandag - Cubero, Mary Kesselyn D. (2015)
Religious architecture has been active since the beginning of time yet it only focuses on the church, its symbolisms and designs. The Church in the Philippines uses the Episcopal Polity as its method of governance, wherein the office of the Bishop is a key authoritative role. Each member of the polity has its own corresponding duties and responsibilities that require different physical spaces. Architects and designers incorporated these conditions of users? satisfaction in the design of church complex. Then again, participatory planning is by far the best option in solving problems of users? satisfaction, since it is a community dilemma. However, participatory planning has loopholes with regards to data integration. Thus, three types of participatory were used in this research: Integrated Design Charrette, Jigsaw Map Making and Photo Writing Wrap-Up and Design Jigsaw. It was concluded that there is dissatisfaction among users of the present complexes. There exists a dissatisfaction of direct users because of lack of necessary spaces and proper planning. All existing complexes have different deficiencies. The episcopal polity has a diocesan curia that divides every individual into different task. The hierarchy of power was reflected through spaces and structures. The necessary general spaces are Church, Parish Pastoral Council (PPC) building, Parish Rectory, Office of the Parish Secretary, Multi-purpose Hall, Prayer Area, Music Room, Open space for events, Recreation Area, Dormitories for Staff, Public Comfort Rooms and Parking Area Simple design guidelines were produced using the data. There were 3 basic issues that mattered, the planning of site, buildings, and interior spaces. The site must have a proper circulation following a circular movement, the buildings and interior spaces must be rectangular for optimal use of spaces.